Avaliações da audiçaõ periférica e central em pré-escolares com toxoplasmose congênita diagnosticada e tratada no primeiro ano de vida - Sabrina Araujo Dornelas (2013)
Introduction: Audiology deficits should be early diagnosed to enable rehabilitation and adequate child development. Congenital toxoplasmosis is a risk indicator for hearing loss. In Brazil, the elevated prevalence of this infection and lack of information regarding audiological assessment of this population motivated this study. Aims: Evaluate the efferent auditory pathway in children with congenital toxoplasmosis early diagnosed and treated in the first year of life, through the analysis of tympanometric results, acoustic reflexes and transient otoacoustic emission suppression, compared to children without risk indicators for hearing loss. Methods: Cross-sectional descriptive study, that took place in the Audiological service of an university hospital. Study population were 150 children with congenital toxoplasmosis, with ages between 3 and 6 years old, from a group diagnosed by the Minas Gerais State Neonatal screening program between november 2006 and may 2007. Participants were evaluated with tympanometry, acoustic reflex, transient evoked otoacoustic emissions (TEOAE) and TEOAE suppression. From the children in the study, 23 were randomly selected and their efferent auditory responses were compared with 23 children without risk indicators for hearing loss. Both groups, comprising 46 ears each, had records of TEOAE and suppression of TEOAE. Statistical analysis was performed with SPSS software, version 17.0. Research was approved by the ethics committee of the institution (UFMG). Results: From the sample analysis it was observed a major incidence of male gender (59,3%), type A tympanometry (91,7%) and presence of acoustic reflexes (60-75%). However, acoustic reflex was absent in 25-40% of cases, independently of tested frequency. Regarding suppression, it was observed equal proportion for right and left ears (77,5% presence and 22,5% absent). There was not discordance (p=0,87) between the answers relative to suppression among the ears (66,7% accordance). Also, there was no discordance between acoustic reflex presence and TEOAE suppression for tested frequencies in the right ear and for the frequencies 0,5; 1,0 e 2,0 KHz in the left ear. Comparison between the groups did not reveal laterality influence in signal amplitude (p>0,05). Congenital toxoplasmosis group had elevated amplitude difference between absence conditions e presence of white noise comparing to the group without risk indicator (p=0,021). Suppression was present in 80% of children, in both groups and when present, signal magnitude was significantly bigger (p=0,009) in the group without risk indicator. Conclusion: In the present study, was possible to observe that children with congenital toxoplasmosis early diagnosed and treated with ages between 3 and 6 years old did not present efferent auditory pathway problems. Type A tympanometric curve and presences of acoustic reflexes were predominant. In the comparison of suppression results and acoustic reflex there was no discordance for most analyzed responses. However absence of acoustic reflex in 4000Hz and absence of TEOAE suppression should be considered even in a lesser proportion. Such findings often relate to auditory processing disorders (APD). New studies are necessary to evaluate the relation between congenital toxoplasmosis and APD.